A New Time-Dependent Limit-Equilibrium Model to Understand Progressive Failure in Bedrock Slopes on the Grimsel Pass - Zapata Torres, Marco Fernando (2019)
Rockfalls can have serious consequences. Therefore, it is important to understand the processes to apply security measures. Limit equilibrium methods (LEM) are models used due to their simplicity and reliability to evaluate rock mass instabilities. Despite the advantages, LEMs assume temporally invariable conditions. The objective is the implementation of a temporally varying condition (progressive tensile edge cracking) in the LEM with the aim of performing a time-dependent analysis. The code combines LEM with crack growth theory to evaluate growth evolution. When a crack begins to propagate, it is selected between the Paris or Charles law of crack growth, choosing the fastest. During propagation, the code records the crack opening, length, iteration, and propagation time until it reaches a critical state. The retrospective analysis used a digital elevation model (DEM) of the Grimsel Pass (Switzerland). The model results help to understand the evolution of tensile crack propagation and new modules can be added to the model. However, the model has limitations and the results should be carefully evaluated.